ALGUNOS FUNDAMENTOS DE LA FILOSOFÍA REALISTA DE SANTO TOMÁS DE AQUINO PARA UNA VALORACIÓN DE LA INTELIGENCIA ARTIFICIAL (IA). - Ocampo Ponce, Manuel (Revista Perseitas)
In 1956, the term artificial intelligence (AI) was introduced to refer to a technology that is capable of emulating the cognitive operations of the human being through the use of computer systems and computer programs in order to help decision-making in different areas of knowledge. However, it has been questioned whether the adjective intelligence should be used for these uses of digital technology. Concern has also been raised about its ethical implications because artificial intelligence consists of non-autonomous systems that are not capable of free and responsible acts, which requires that they be guided by people. The purpose of this paper is to present some foundations of the realistic philosophy of Saint Thomas Aquinas that allow us to make an assessment of artificial intelligence.